The Middlemore Boys:: Immigration, Settlement, and Great War Volunteerism in New Brunswick - Mainville, Curt (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2013)
Between 1885 and 1916, Sir John Middlemore’s Children’s Emigration Homes resettled more than 3,000 indigent British youth from the streets of Birmingham to Maritime farms. While their transition was anything but easy, these emigrants were more than mere reactionaries to circumstance. Fifty-four per cent of New Brunswick’s Middlemore boys volunteered for military service with the Canadian Expeditionary Force with the onset of the Great War (almost one in six were underage). While motivations for enlistment varied,)many Middlemore boys had an overwhelming need to return to the familiarity of home and to reconnect)with family members once left behind.